Prognostic performance of the 'DICA' endoscopic classification and the 'CODA' score in predicting clinical outcomes of diverticular disease: an international, multicentre, prospective cohort study. Issue 7 (26th October 2021) - Tursi, Antonio; Brandimarte, Giovanni; Di Mario, Francesco; Elisei, Walter; Picchio, Marcello; Allegretta, Leonardo; Annunziata, Maria Laura; Bafutto, Mauro; Bassotti, Gabrio; Bianco, Maria Antonietta; Colucci, Raffaele; Conigliaro, Rita; et al.
Abstract : Objective: To investigate the predictive value of the Diverticular Inflammation and Complication Assessment (DICA) classification and to develop and validate a combined endoscopic-clinical score predicting clinical outcomes of diverticulosis, named Combined Overview on Diverticular Assessment (CODA). Design: A multicentre, prospective, international cohort study. Setting: 43 gastroenterology and endoscopy centres located in Europe and South America. Participants: 2215 patients (2198 completing the study) at the first diagnosis of diverticulosis/diverticular disease were enrolled. Patients were scored according to DICA classifications. Interventions: A 3-year follow-up was performed. Main outcome measures: To predict the acute diverticulitis and the surgery according to DICA classification. Survival methods for censored observation were used to develop and validate a novel combined endoscopic-clinical score for predicting diverticulitis and surgery (CODA score). Results: The 3-year cumulative probability of diverticulitis and surgery was of 3.3% (95% CI 2.5% to 4.5%) in DICA 1, 11.6% (95% CI 9.2% to 14.5%) in DICA 2 and 22.0% (95% CI 17.2% to 28.0%) in DICA 3 (p<0.001), and 0.15% (95% CI 0.04% to 0.59%) in DICA 1, 3.0% (95% CI 1.9% to 4.7%) in DICA 2 and 11.0% (95% CI 7.5% to 16.0%) in DICA 3 (p<0.001), respectively. The 3-year cumulative probability of diverticulitis and surgery was ≤4%, and ≤0.7% in CODA A; <10% and <2.5% in CODA B; >10% and >2.5% in CODA C, respectively. The CODA score showed optimal discrimination capacity in predicting the risk of surgery in the development (c-statistic: 0.829; 95% CI 0.811 to 0.846) and validation cohort (c-statistic: 0.943; 95% CI 0.905 to 0.981). Conclusions: DICA classification has a significant role in predicting the risk of diverticulitis and surgery in patients with diverticulosis, which is significantly enhanced by the CODA score. Trial registration number: NCT02758860 .